Evaluating Competence-Based Vocational Education In Indonesia - Ahmad Basahil; Sabarun Sabarun; Zaitun Qamariah (Jurnal Pendidikan dan Sastra Inggris, 2023)
The study “Evaluating Competence-Based Vocational Education in Indonesia” investigates at the CBE is used in Indonesian vocational education. In addition to gathering cross-sectional survey data from 41 school administrators, 453 instructors, and 2219 students from 41 schools, the study examines educational policy texts. The study looks at how much CBE is implemented in Indonesian vocational education. In terms of the improvement of students’ competencies, the study also assesses the success of CBE implementation. The study comes to the conclusion that CBE implementation in Indonesian vocational education is still in its early stages and that there are still many issues that need to be resolved in order to ensure effective CBE implementation.